High temperature oxidation behavior of MoSi2–Al2O3 composite coating on TZM alloy. Issue 8 (15th April 2022) - Liu, Zhanggen; Li, Wei; Fan, Jinglian; Lv, YaoZha; Wang, Zhenwei; Zhao, Xiaojun
Abstract: A novel MoSi2 –Al2 O3 composite coating was prepared on Mo-based TZM alloy by slurry sintering method. The oxidation behavior of the coating was evaluated at 1600 °C in static air. Microstructure and phase composition of the as-prepared and oxidized coatings were characterized, and the antioxidant mechanism of the coating at high temperature was discussed. A three-layer structure was observed in the as-prepared coating, consisting of a ∼2 μm thick Mo5 Si3 diffusion layer, a ∼65 μm thick MoSi2 inner layer and a ∼36 μm thick outer layer of mixture of MoSi2 and Al2 O3 . After oxidation at 1600 °C for 5 h, all MoSi2 phases were completely converted to intermediate silicide Mo5 Si3 by solid-state diffusion, and the formed Mo5 Si3 phase would be transformed into Mo3 Si phase with further extending the oxidation time. Furthermore, a dense oxide layer of SiO2 -mullite was formed on the specimen surface, which can effectively protect the material to further oxidation. The MoSi2 –Al2 O3 coating could protect the substrate effectively at 1600 °C for 20 h without failure. The enhanced oxidation resistance of MoSi2 –Al2 O3 coating is due to the formation of multi-layer structure containing a SiO2 -mullite composite oxide outer layer with high thermal stability and low oxygen permeability.